Gendersensible Gestaltung des neuen Studiengangs "BWL - Digitale Wirtschaft" an der Beuth Hochschule für Technik Berlin - Brandt, Martina (Schriftenreihe des Gender- und Technik-Zentrums (GuTZ) der Beuth Hochschule für Technik Berlin "Gender Diskurs", 2017)
The advancing digitalisation is leading to a fundamental change in the world of work. So far, women have not taken advantage of the associated career opportunities to the same extent as men. A gender-sensitive design of degree programmes can make a significant contribution to changing this situation. This publication examines which measures were taken to this end in the new "Business Administration - Digital Economy" course at Beuth University of Applied Sciences. In addition, relevant experiences and good practices from other universities are presented and the possible gain of knowledge on career goals and career requirements from surveys of students and graduates is discussed.